Diffusion Tensor Imaging of Epileptogenic Lesions in TSC - Divakar Mithal; Maura Ryan (Pediatric Neurology Briefs Publishers, 2016)
Investigators from University of California Los Angeles, studied whether epileptogenic tubers in Tuberous Sclerosis Complex (TSC) can be identified by diffusion tensor imaging (DTI).